丹戎布拉大学师范教育学院汉语专业 2020 届学生对 语气助词“吗 ”、 “呢 ”与 “吧 ”的掌握情况分析 - Dewi Lestari Lukman; Ina Ina; Bun Yan Khiong (Universitas Tanjungpura, 2022)
AbstractThe word modality particle is used to give additional meaning in grammar, this particle word is usually called a modality which is also commonly called a particle. Although there are differences in the use of these three words, students sometimes still don't understand in what situations they should use the words